Gross Anatomy of Mouth Cavity of Kadaknath Fowl (Gallus domesticus) - Verma, Rakhi (Indian Journal of Veterinary Anatomy, 2021)
In the mouth cavity of 7th, 13th and 50th week aged Kadaknath fowls, the dense horny beak was lying over the incisive bone and mandible. The lower beak was overlaid by the upper beak. A longitudinal fissure was observed in the mid line of hard palate, characterized by a narrow rostral portion and an enlarged caudal portion. A long infundibular cleft represented the common opening of two auditory tubes. The hard palate had a median swelling and two lateral palatine ridges. Caudally pointing papillae were arranged in single transverse row. The floor of the oropharynx was formed by the interramal region, the tongue and the laryngeal mound. The length of triangular shaped tongue was 1.1±0.02 cm at 7th week, 1.6±0.31 cm at 13th week and 1.6±0.07 cm at 50th week aged fowl. The laryngeal mound was presented caudal to the tongue, in which the glottis (laryngeal cleft) was present. The posterior limit of pharynx on upper part had single row of papillae, while the lower part had two rows of papillae in all the three age groups. All these structures help in feeding, watering and fighting of the birds.